Managing Against the Development of Herbicide-Resistant Weeds: Sugarcane - Dennis C. Odero; Brent A. Sellers; Jason A. Ferrell; Gregory E. MacDonald (EDIS)
Although it is likely that small populations of herbicide-resistant weeds are already present in the Everglades Agricultural Area (EAA), herbicide resistance is currently not a significant problem. The continued use of integrated and properly managed weed control programs should ensure that resistance does not become a major issue in the future. In order to successfully manage herbicides against the development of herbicide-resistant weeds, you must have a basic understanding of which herbicides have the same site of action. This revised 4-page fact sheet lists herbicides by group number, site of action, chemical family, common name, and trade name. Written by D.C. Odero, B.A. Sellers, J.A. Ferrell, and G.E. MacDonald and published by the UF Department of Agronomy, March 2011.